The effects of rotation crops on survival of root-knot, root-lesion and spiral nematodes: efecto de rotacion de cosechas sobre la supervivencia de nematodos noduladores, lesionadores y espiraliformes - Wilson, G.F.; Caveness, F.E. (1980)
Potential rotation crops for replacement of natural soil regeneration in tropical agriculture were grown in nematode infested soil following Celosia argeniea. The aggregate nematode population mean was one-third the preplant mean after six months. Meloidogyne incognita juvenile soil populations were reduced under 15 crops and maintained under three. Helicotylenchus pseudorobustus populations were reduced under eight crops and maintained under 10. Pratylenchus sefaensis were maintained under 17 crops and significantly increased under Crotalaria juncea.